Early human follicle ultrastructure comparison after slow cryopreservation in two different cryoprotectants - Els, Cecilia Lydia (Stellenbosch : Stellenbosch University, 2008)
Thesis (MScMedSc (Obstetrics and Gynaecology))--Stellenbosch University, 2008.